Peran Keluarga Dalam Pendidikan Islam - Bain, Muhammad Nur; Mustonef; Mubarokah, Azwirotul (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
The purpose of this study is to understand how families contribute to shaping children's religious identity through Islamic education in the home environment. Family education builds the first basic moral and spiritual foundation for children, which helps them develop attitudes and behaviors that are in accordance with the values instilled. This study uses a literature review method to investigate various theories and findings related to the role of the family in Islamic education, based on analysis of text sources and previous research. Thus, it can be concluded that the family has a very large role in the growth and development of children, both in terms of intellectual, moral, and religious. Parents play a central role in educating their children according to Islamic values, through education, guidance, supervision, and providing good examples. Achieving the goals of Islamic education depends not only on the quality of individual parents, but also the quality of the family as a whole, as well as the importance of harmonious cooperation in the surrounding environment. A supportive environment, both physically and socially, also plays an important role in helping children grow and develop according to the teachings of Islam.